Combinatorial effects of Zingiber officinale and Citrus limon juices: Hypolipidemic and antioxidant insights from in vivo, in vitro, and in silico investigations - Bekkouch, Oussama; Bekkouch, Ayoub; Elbouny, Hamza; Touiss, Ilham; Assri, Soufiane El; Choukri, Mohammed; Bourhia, Mohammed; Kim, Kiryang; Kang, Sojin; Choi, Min; Choi, Jinwon; Kim, Hyo Jeong; et al. (PLOS ONE, 2025)
The combined use of Zingiber officinale (ginger) and Citrus limon (lemon) has been traditionally recognized for its therapeutic potential, particularly in promoting cardiovascular health. However, the synergistic effects of these botanicals on hyperlipidemia and oxidative stress, two major contributors to cardiovascular disease, remain insufficiently characterized. This study employed an integrative approach involving in vivo, in vitro, and in silico methodologies to assess the hypolipidemic and antioxidant properties of ginger and lemon juices. In vivo experiments were conducted using a murine model of Triton WR-1339-induced hyperlipidemia. Antioxidant activity was evaluated through DPPH and ABTS assays, while molecular docking simulations were performed to assess interactions with HMG-CoA reductase, a key enzyme in cholesterol metabolism. Phytochemical profiling revealed high levels of bioactive compounds, with ginger juice containing 6-gingerol (15.54% peak area), and lemon juice rich in hesperidin (13.85%) and rutin (5.57%). These constituents likely contributed to the observed pharmacological effects. The combined formulation led to marked improvements in lipid parameters, including reductions in total cholesterol (−54.3%), triglycerides (−49.8%), and LDL-C (−58.1%), alongside an increase in HDL-C (+47.6%) compared to hyperlipidemic controls (p < 0.05). Antioxidant assays further demonstrated strong free radical scavenging activity, with IC₅₀ values of 30.92 ± 2.00 µg/mL (ABTS) and 44.94 ± 1.02 µg/mL (DPPH) for the combined formulation. Molecular docking confirmed high binding affinities of key compounds, with hesperidin and 6-gingerol displaying binding energies of −10.4 and −9.6 kcal/mol, respectively, against HMG-CoA reductase. In summary, the combination of Zingiber officinale and Citrus limon juices exhibited potent lipid-lowering and antioxidant activities, outperforming the effects observed with individual extracts. These findings underscore their potential as natural therapeutic agents for the management of hyperlipidemia and oxidative stress. Further clinical investigations are warranted to validate these preclinical results and to explore their future application in the development of nutraceuticals or functional foods.